Effects of sport on static balance in athletes with visual impairments - Bednarczuk, G.; Wiszomirska, I.; Rutkowska, I.; Skowronski, W. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Proper balance is crucial for postural control and physical activity performance. Issues related to balance as well as effects of various factors on balance are in the center of attention of specialists in a number of fields including sport. Research results show that every sports discipline demands different motor preparation (including balance) and persons with visual impairments exhibit worse balance compared to their sighted counterparts. Therefore, this study sought to assess static balance in athletes with visual impairments with reference to the type of sport they did, the length of their training experience, training loads and dysfunction level. METHODS: The study involved 57 men (shooters, tandem cyclists, football and goalball players) with visual impairments. AMTI stabilographic platform was used to assess static balance. The study participants performed the following tests: standing on both feet with eyes open and closed and single-leg stance with eyes open and closed. RESULTS: Balance in tests performed while standing on both feet did not differentiate athletes in terms of the sport they did. Static balance of athletes with visual impairments significantly differs in the single leg stance. Better balance was observed in tests with eyes open. Taking into consideration sports disciplines practiced by the athletes, significant differences in balance in single left leg tests with eyes open and closed were observed. Athletes training more than five hours per week manifested better balance compared to those who practiced less than five hours per week. CONCLUSIONS: The findings indicate that athletes performing particular sports may use strategies of maintaining balance that result from the structure of these sports. The lack of differences in balance among athletes with different degrees of dysfunction may indicate their high fitness levels and show how balance is affected by physical activity performance. Results of the analysis of balance with regard to the length of training experience may suggest that it is not this factor but rather the quality of training that may exert an influence on this ability.